EVALUASI PENGARUH TIMBUNAN DAN STOCKYARD PANCANG TERHADAP KEGAGALAN PANCANG (STUDI KASUS: PROYEK JEMBATAN X DI KALIMANTAN) - Matheus, Patrick; Hartono, Darwin; Sukamta, Sukamta; Sadono, Kresno Wikan (Rang Teknik Journal, 2025)
One of the bridge projects in Kalimantan is built on soft soil. Soft soil has poor bearing capacity, low shear strength and permeability, and high compressibility. One of the substructures of the bridge project, consisting of two spun pile points, experienced failure (exceeding the allowable inclination, indications of breakage at a depth of -8,000 mm, and failure to achieve the planned bearing capacity). The failure occurred after excavation for the pile cap was carried out.The additional load from preloading embankments and a spun pile stockyard, located 20,000 mm and 15,000 mm away, caused lateral deformation in the existing soil. This lateral deformation influenced additional deformation and bending moments in the failed spun piles. An evaluation of the additional load on the spun piles was conducted using the Finite Element Method with Plaxis 2D software. The additional load from the preloading embankments and stockyard was analyzed to determine its impact on the spun piles.The analysis showed that the additional load from the preloading embankments and stockyard caused lateral deformation, leading to deformation and bending moments in the spun piles. However, this additional load alone was not sufficient to cause failure in the spun piles.